Valuing the Benefits of Rock Climbing and the Welfare Gains from Decreasing Injury Risk. Issue 11 (20th August 2018) - Nicita, Lea; Shaw, W. Douglass; Signorello, Giovanni
Abstract: Rock climbing is an increasingly popular recreation activity worldwide, nevertheless there are only few studies that estimate the demand for it. In this article the Kuhn–Tucker approach is used to estimate the demand for rock climbing in Sicily, the recreation value of different climbing sites, and the welfare impact of reducing injury risk. In modeling the demand for climbing we account for the heterogeneity of preferences. We find that decreasing the level of injury risk generates remarkable welfare gains to climbers. This is the first study we know of that provides a welfare measure of risk reduction in rock climbing and one of a very few studies in environmental economics that uses a revealed preference approach to estimate a welfare measure associated with a reduction in risk.